2002
DOI: 10.1590/s0101-81752002000600003
|View full text |Cite
|
Sign up to set email alerts
|

Moluscos em área de horticultura no município de Porto Alegre, Rio Grande do Sul, Brasil

Abstract: ABSTRACT. Mollusca in horticultural production area in Porto Alegre county, Rio Grande do Sul, Brazil. Horticultural production areas are favorable to development and maintenance of land mollusks populations. To know the mollusk fauna diversity in that kind of production area a research project was conduced in a rural-urban district of Porto Alegre, Rio Grande do Sul, Brazil. The production property studied is located in lhe Southern zone of the city and has 17 ha of cu ltivated area. Culturas de hortaliças co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(3 reference statements)
1
1
0
2
Order By: Relevance
“…These mollusks cause lesions in the leaves, compromising the quality of the plant, and contaminate them with their feces. These data confirm the report of Imenes et al (2000) but contradict the results reported by Bruschi-Figueiró and Veitenheimer-Mendes (2002), who considered B. similaris an accidental species.…”
Section: Resultssupporting
confidence: 88%
“…These mollusks cause lesions in the leaves, compromising the quality of the plant, and contaminate them with their feces. These data confirm the report of Imenes et al (2000) but contradict the results reported by Bruschi-Figueiró and Veitenheimer-Mendes (2002), who considered B. similaris an accidental species.…”
Section: Resultssupporting
confidence: 88%
“…For instance, one study in Pennsylvania in the United States showed that four out of 15 field-occurring slugs are invasive (Douglas & Tooker, 2012). Similarly, a study on horticultural crops in the Rio Grande do Sul state (south Brazil) reported that among the six gastropod species occurring on Brassica crops, four were invasive and more frequent (up to 82% frequency) than the native ones (Bruschi-Figueir o & Veitenheimer-Mendes, 2002). Thus, our findings agree with previous studies reporting a higher abundance of invasive species on arable crops (Bruschi-Figueir o & Veitenheimer-Mendes, 2002;Douglas & Tooker, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…7) Área de coleta na EFMA: Área peridomiciliar. -TEIXEIRA et al, 1993;BARKER, 1999;MAURER et al, 2002;BRUSCHI-FIGUEIRÓ;VEITENHEIMER-MENDES, 2002;THOMÉ et al, 2006;OHLWEILER et al, 2010;ALEXANDRE et al, 2017). Área de coleta na EFMA: Área de mata recuperada.…”
Section: Coleta Fixação E Identificação Dos Gastrópodesunclassified